Digital literacy, remote teaching and access during COVID-19 pandemic: Impacts on postgraduate female in Brazilian Amazon - Cícero da Silva; Fabiana Komesu; Cédric Fluckiger (Universidad de Costa Rica, 2023)
The aim of this article is to understand how digital literacies, the usage of digital technologies and emergency remote teaching during the COVID-19 pandemic have affected the life of women participating in stricto sensu Graduate Programs of Universities in the Brazilian Legal Amazon. This study is based on the perspective of digital literacies, which considers the social uses of reading and writing. This is a mixed approach, exploratory and applied research. The data has been collected during August and September, 2021, by means an online platform, based on a 30-item semi-structured questionnaire. The data set comprises 218 valid answers from female professors (n = 100) and students (n = 118) (age 18+) of the surveyed Universities. The results show that the respondents have faced many challenges in emergency remote teaching during the pandemic, in particular, work overload, scarce interaction with colleagues, limitations in the use of digital technologies, difficulties in accessing digital technologies, mental/physical health problems and lack of boundaries between academic and family activities performed in the household environment. Nonetheless, the digital technologies have enabled them to participate in events (livestreams, webinars, conferences, courses), meeting research groups and proceed with classes and research. In a geographically large and economically disadvantaged region, as is the case of the Brazilian Legal Amazon, public policies are essential in order to promote literacy events and activities.